OPTIMIZATION OF CELLULASE PRODUCTION WITH PENICILLIUM NALGIOVENSE Sll GROWN ON PRETREATED WHEAT POLLARD - TRESNAWATI PURWADARIA; AGNES T. KUMALASARI; TUTIHARYATI; PIUS P. KETAREN; ARNOLD P. SINURAT1 (SEAMEO BIOTROP, 2004)
The cellulase production with Penicillium nalgiovense S11 on wheat pollard was enhanced using substrate pretreatments, i.e.: (i) mechanic process by Wiley milling, (ii) reducing sugars removal by water soaking, and (iii) chemical pretrcatment by 0.5% NaOH soaking at 100°C. The enzyme production stated as enzyme activities of all prctrcated substrates were higher than the untreated substrate. Although soaking with water showed significant increase in enzyme activities, the highest CMCase (EC 3.2.1.4), FPase (filter papcrase) and p-glucosidase (EC 3.2.1.21) were observed on NaOH pretreated pollard. The NaOH prctreatment also enhanced the enzyme production by increasing substrate concentration from 2 to 4%. The optimal incubation time in the cellulase production on 4% NaOH-pretrcated pollard was observed on the fifth day. Addition of 250 ppm glucose also increased the enzyme activities. The optimal treatments increased the specific activities of CMCase, FPase, and |3-glucosidase into 60, 4, and 198 times, respectively, as compared to the specific activities on 2% unpretreated pollard. Keywords : Cellulase production/ pollard pretreatments/ water soaking/ NaOH soaking